Torsional springback analysis in thin tubes with non-linear work hardening / Vikas Kumar Choubey, Mayank Gangwar and J. P. Dwivedi - Choubey, Vikas Kumar; Gangwar, Mayank; Dwivedi, J. P. (UiTM Press, 2010)
A theoretical analysis of the springback of thin tubular sections of non linear work-hardening materials under torsional loading has been carried out. The non-linear behavior of the material is approximated by using Modified Ludwik type stress-strain relation. The theoretical analysis is supported by experimental results for different tubular section viz. square, triangular and rectangular sections of different thicknesses. Finally analytical generalized expressions relating angle of twist to twisting moment and residual/springback angle of twist per unit length for thin tubular bars under plastic torsion are obtained in non-dimensionalized form. A comparison between the results obtained for thin tubes on non-linear and linear work-hardening material loaded under torsion is also made.